2020
DOI: 10.1016/j.cub.2020.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Response to Tensile Stress Is Curbed by NEK6 to Buffer Growth Variation in the Arabidopsis Hypocotyl

Abstract: Highlights d An hyper-response to mechanical stress can lead to increased phenotypic variability d NEK6 exhibits a bipolar recruitment on microtubules that align with tensile stress d The nek6 wavy phenotype is consistent with a hyperproprioceptive response d Growth rate uncouples shape-and growth-derived stress response in nek6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…Nastic movement of leaves and stems further suggest that variations in the mechanical status of the plant are subcircadian (30). The analysis of hypocotyl growth also suggests that shorter period fluctuations exist in Arabidopsis seedlings, from which our protoplasts were extracted (31). Last, the calcium waves at the shoot apical meristem, every 10-30 min, may indicate that mechanical fluctuations in plant tissues are underestimated (32).…”
Section: Discussionmentioning
confidence: 93%
“…Nastic movement of leaves and stems further suggest that variations in the mechanical status of the plant are subcircadian (30). The analysis of hypocotyl growth also suggests that shorter period fluctuations exist in Arabidopsis seedlings, from which our protoplasts were extracted (31). Last, the calcium waves at the shoot apical meristem, every 10-30 min, may indicate that mechanical fluctuations in plant tissues are underestimated (32).…”
Section: Discussionmentioning
confidence: 93%
“…To confirm that such shape descriptors are pertinent, and knowing that cortical microtubules are well-known pavement cell shape regulators, we used mutants with microtubule defects as positive controls. We performed the same analysis on mutants with a reported enhanced microtubule response to stress ( nek6 (Takatani et al, 2020)) and a reported reduced response to stress ( bot1 (Uyttewaal et al, 2012). We also included lines with tubulin mutations affecting microtubule dynamics ( tua3 D205N , tua4 S178Δ , and tua6 A281T referred as tua3 , tua4 and tua5 in the following (Ishida et al, 2007)(Matsumoto et al, 2010)) and spr2 with a reported enhanced cortical microtubule response to stress (Hervieux et al, 2016) but also ambivalent regulatory role in microtubule severing depending on tissue (Wightman et al, 2013)(Fan et al, 2018)(Nakamura et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Turgor pressure levels are monitored by two main families of proteins localized in different subcellular compartments, including chloroplasts and the plasma membrane: histidine kinases and channel complexes. Furthermore, new evidence from observations in A. thaliana seedlings points to a third mechanosensitive system, in which microtubules acting as tension sensors regulating developmental processes contribute also to mechanosensing in plant cells [65,66].…”
Section: Perception Of Turgor Pressure and Mechanical Stimuli In The mentioning
confidence: 99%